Enhancing high-quality education through systemic school leadership: a systematic review - Robert White; Charles Lowery; Jerry Johnson (Quality Education for All)
Purpose – This paper aims to examine systemic school leadership and identify effective leadership practices across policy, organizational and instructional levels while exploring their interactions in fostering inclusive educational environments. Design/methodology/approach – A rigorous search strategy adhering to PRISMA guidelines was used, followed by a convergent integrated approach to evidence synthesis. Empirical studies from 2014 to 2024 were analyzed using grounded theory techniques. Findings – Five key themes emerged: collaborative leadership, equity-focused decision-making, pedagogical leadership and professional development, building a community of support and data-driven practices. Analysis revealed distinct patterns in how different leadership approaches contribute to inclusive education. The central role of instructional leadership and pedagogy emerged as crucial for successful implementation. Challenges include systemic barriers, resistance to change, resource constraints and managing diverse needs. Research limitations/implications – Most included studies were short term and conducted in economically advanced Western countries, highlighting the need for longitudinal research in diverse global contexts. Practical implications – Findings offer actionable insights for policymakers and practitioners on how to integrate instructional leadership with systemic approaches to foster inclusive education, particularly emphasizing the role of pedagogical leadership and professional development. Social implications – Effective inclusive leadership in schools contributes to the development of more equitable and cohesive societies. Originality/value – This review provides a comprehensive synthesis of recent empirical evidence on systemic school leadership for inclusive education, specifically examining how different leadership approaches interact across policy, administrative and instructional domains to promote inclusive practices. It offers a holistic framework for understanding how leaders can work systematically to address barriers to inclusion at multiple levels.